Usage and Impact of Artificial Intelligence on Accounting: Evidence from Malaysian Organisations - Lee, Cheah Saw; Tajudeen, Farzana Parveen (Asian Journal of Business and Accounting, 2020)
Manuscript type: Research paper Research aims: This study aims to investigate the use and impact of artificial intelligence (AI)-based accounting software among organisa-tions in Malaysia. Design/Methodology/Approach: Face-to face interview is performed with representatives from nine organisations that are using AI-based accounting software. Constant comparative method is used to analyse the data collected. Research findings: The results highlight various adoptions of AI-based accounting software across the organisations. These are mainly used as a tool to deposit document images, to capture invoice infor-mation automatically, to monitor invoice approvals, to manage risks and also to track users’ activities. The use of AI-based accounting software has accelerated productivity, improved efficiency, enhanced customer service, supported the flexible working style, increased pro-cess governance as well as saved manpower. Theoretical contribution/Originality: This study fills the research void by providing insights into how the AI-accounting software is used, thereby benefitting organisations in Malaysia. With the arrival of industry revolution 4.0, comprehensive knowledge on the usage of AI is pertinent. The findings of this study may also serve as a foundation for future research in AI adoption. Practitioner/Policy implication: The findings of this study encourage industries to consider the usage of AI-based accounting software in the management of their accounts payable functions. It also provides useful guidance for practitioners on how the AI-based accounting software can be effectively applied as part of the innovation process. Research limitation/Implications: Since the scope of this study only involves the accounting service provider, the generalisation of this study may be limited. Keywords: Artificial Intelligence, Accounting, AI, Malaysia, Payable, Qualitative JEL Classification: M150, M41